Metacognition and Its Relationship to Critical Thinking among High-Achieving Secondary School Students (Journal of Imam Al-Kadhim College, 2025)
This study aims to explore the relationship between metacognition and critical thinking among high-achieving high school students. Metacognition refers to an individual's awareness and regulation of their thinking processes, while critical thinking involves analyzing information and making logical decisions. The study employed a descriptive correlational research design and included a sample of 200 high-achieving students from Baghdad during the 2023-2024 academic year. Two scales were developed to measure metacognition and critical thinking, and their validity and reliability were confirmed through statistical tests                                                                                  The results indicated that high-achieving students exhibited high levels of both metacognition and critical thinking. Additionally, a moderate positive correlation was found between metacognition and critical thinking, suggesting that enhancing metacognitive skills may contribute to improving critical thinking abilities. The study recommends integrating metacognitive and critical thinking strategies into curricula and employing interactive teaching methods to support these skills
Keywords: Metacognition ,Critical Thinking, Outstanding students, Preparatory; Metacognition; Critical Thinking; Outstanding students; Preparatory